Design and evaluation of a decentralised information service architecture for IEEE 802.21 networks. (27th May 2014) - Buiati, Fábio; Villalba, Javier García; Cañas, Delfín Rupérez; Corujo, Daniel; Aguiar, Rui L.
The deployment of wireless technologies such as Wi–Fi, WIMAX and LTE brings to the mobile user the opportunity to switch from one network to another, in a seamless manner. To accomplish this, the user must be able to discover which types of network connectivity are available. The IEEE 802.21 standard specifies a media independent information service (MIIS) providing capabilities for discovering network information within a geographical area. The representation and distribution of mobility information in heterogeneous networks are a big challenge, especially in multi–operator environments. In this paper, we introduce a decentralised information service architecture that improves the user experience and ensures scalability for large system deployments. Additionally, an evaluation using the NS–2 network simulator is presented. The results demonstrate that our proposal outperforms the existing approaches in terms of query delay, users optimal handovers and communication overhead, contributing to a traffic decrease at the operators core network and internet.